Green manuring in the recovery of degraded oxisoil fertility - Alcântra, Flávia Aparecida de; Neto, Antonio Eduardo Furtini; Paula, Miralda Bueno de; Mesquita, Hugo Adelane de; Muniz, Joel Augusto (Pesquisa Agropecuaria Brasileira, 2000)
The experiment was conducted at the Empresa de Pesquisa Agropecuária de Minas Gerais, Nova Baden Experimental Station, in Lambari, MG, Brazil, aiming at evaluating the performance of the green manures pigeonpea (Cajanus cajan (L.) Millsp.) and sunnhep (Crotalaria juncea L.) with and without incorporation of the biomass, on the recovery of fertility of degraded soil cultivated with brachiaria (Brachiaria decumbens Stapf.). Experimental design used was of randomized block in factorial scheme of split plots with three replications, putting the biomass handling in the plots and both the legumes and brachiaria in the subplots. The three crops were cut and handled at the late flowering stage of the legumes, when samplings of the plant material were done for assessing dry matter yield, concentration and amount of nutrient. Evaluations of soil samplings at six depths (0-5, 5-10, 10-20, 20-40, 40-60 e 60-80 cm) and three periods (90, 120 and 150 days after handling) were performed. Pigeonpea stood out in the first evaluation concerning the improvements in soil fertility and sunnhep and slower mineralization, in the second. In the third evaluation, no benefits from the green manure on the chemical properties of the soil were found.